East African Agriculture and Climate Change: A Comprehensive Analysis — Uganda - Bashaasha, Bernard; Thomas, Timothy S.; Waithaka, Michael; Kyotalimye, Miriam (International Food Policy Research Institute, 2012)
Uganda occupies a total area of 241,038 square km, most of which is suitable for agriculture. Sixteen percent of the total area is water and swamps, while 7 percent is forested. Maize, beans, cassava, and banana (plantain) are the most widely grown crops. Uganda’s climate is regarded as its most valuable natural resource, one central to the livelihoods of many Ugandans. However, the last few decades have been marked by climate variability that has given rise to more frequent extreme weather events, such as droughts, floods, and landslides, damaging natural resources and hindering social and economic development. The country’s population grew by 3.7 percent between 2009 and 2010 (to a total of 32 million people). The population is expected to reach 103.2 million in 2050, assuming growth declines to 2.9 percent per annum between 2040 and 2050. The population remains predominantly rural (85 percent in 2010). At 50 years, life expectancy remains low. Malaria is the most prevalent fatal illness. The poverty rate is down from 31 percent in 2006 but, at 24.5 percent, remains high.